La virtù della carità in rapporto con la conformità con la Volontà di Dio - Mestre, Alberto (Alpha omega, 2020)
This article offers a detailed study of the virtue of charity, with the aim of showing how it is the virtue which brings about the greatest degree of conformity of the human will the divine will. Given that «the will is directed principally more towards an end rather than towards that which is for the end» and since it is the final end which is the proper object of charity, the human will is more conformed to the divine will to the extent that is succeeds in living better what charity is in itself. Analysing in what charity itself consists has been of great help to us in clarifying the dynamism involved in conforming the human will to the divine will, leading to the conclusion that it consists in willing that which God wills through charity, in other words, willing as God wills.